2023
DOI: 10.3390/pharmaceutics15020456
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a Medical Grade Thermoplastic Polyurethane for the Manufacture of an Implantable Medical Device: The Impact of FDM 3D-Printing and Gamma Sterilization

Abstract: Three-dimensional printing (3DP) of thermoplastic polyurethane (TPU) is gaining interest in the medical industry thanks to the combination of tunable properties that TPU exhibits and the possibilities that 3DP processes offer concerning precision, time, and cost of fabrication. We investigated the implementation of a medical grade TPU by fused deposition modelling (FDM) for the manufacturing of an implantable medical device from the raw pellets to the gamma (γ) sterilized 3DP constructs. To the authors’ knowle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 34 publications
1
7
0
Order By: Relevance
“…Moreover, TPUs are considered as resilient elastomers, which possess a range of desirable properties such as elastomeric property and resistance to abrasion. , Because of their elastomeric properties, TPU is an excellent material to build shape-memory scaffolds, with the ability to recover the original shape after being subjected to mechanical stresses until they break, as seen by Ahmad et al This trend was also observed in the scaffolds developed in this work. In fact, the scaffolds are able to return to their original shape after mechanical tests when breaking did not occur.…”
Section: Results and Discussionsupporting
confidence: 75%
“…Moreover, TPUs are considered as resilient elastomers, which possess a range of desirable properties such as elastomeric property and resistance to abrasion. , Because of their elastomeric properties, TPU is an excellent material to build shape-memory scaffolds, with the ability to recover the original shape after being subjected to mechanical stresses until they break, as seen by Ahmad et al This trend was also observed in the scaffolds developed in this work. In fact, the scaffolds are able to return to their original shape after mechanical tests when breaking did not occur.…”
Section: Results and Discussionsupporting
confidence: 75%
“…Sterilisation of TPU filaments has been tested in the literature and has been shown not to alter the biocompatibility of the material in terms of cytotoxicity nor the mechanical and geometric properties of the phantom 32 . This was done using the gamma radiation sterilisation method, applying an irradiation of 40 KGy according to ISO 11137‐2.…”
Section: Resultsmentioning
confidence: 99%
“…Autoclave sterilisation and HPGP also have a comparable treatment time (1 h vs. 45 min, respectively). On the other hand, gamma irradiation, the only strategy currently tested and found to be inappropriate for the sterilisation of TPU filament, resulted in 32 . This technique, although also very effective in the weft of the printed piece, has several drawbacks, including long treatment times (from hours to days), management of radioactivity and consequently high costs.…”
Section: Discussionmentioning
confidence: 99%
“…Thermoplastic polyurethanes (TPUs) have numerous applications in medicine due to their physicochemical properties, such as elasticity, thermal resistance, low abrasion, and resistance to aging under physiological conditions, with a simultaneous lack of toxicity to the human body. In cardiac surgery, TPU primarily produces heart valve leaflets and artificial heart components. , TPU is also used to make blood bags, apparatuses for extracorporeal blood oxygenation, breast implants, catheters, dental floss, elements of oxygen masks, bone adhesives, artificial blood vessels, stomach balloons, components of esophageal prostheses, and tendon prostheses. …”
Section: Introductionmentioning
confidence: 99%